INSTITUTIONAL DETERMINANTS — DECORATIONS OR YOKE — A CRISIS TEST - Stankiewicz, Wacław (Ekonomia i Prawo. Economics and Law, 2015)
Institutional determinants of economic crises as a subject of scientific study is a compromise between quality notions and quantity calculation. Under pressure of practical governing and disrupted by crises, economic thought developed some concepts and doctrines, addressed to the state authorities. As attractive component theory of economic cycles come out institutionalism. The concepts of two scholars: Svetlana Kirdina (Russia) and Thráinn Eggertson (Iceland) are worth noting. S. Kirdina promote the theory of an institutional matrix, where the area of conflicts is located. Eggertson is recognized as an author of the theory of imperfect institutions and limit of reform. Interesting issues, both theoretic and practical ones, against the background of Ukrainian drama, may be found in publications of Vladimir Lipov. He developed methodology of institutional economics and focused attention on the theory of goods, especially on dual notions complementary and substitution. As a starting point to an analysis, Lipov proposes the structure of institutional blocs. Progressing gradually and employing the dynamics of blocs cooperation, he justifies the importance of complementary. It provides an opportunity to analyze an institution from a structural and functional angle. In the further section of the paper, Hyman P. Minsky‘s “financial instability hypothesis” is extensively covered and discussed. Among the reasons, the rebirth of Keynesianism and the pressure exerted by the last American crises are listed. Financial instability is blamed very intensively. Given the above, various determinants are obviously necessary but always distant from a perfect resolution.